2022
DOI: 10.3389/fimmu.2021.809808
|View full text |Cite
|
Sign up to set email alerts
|

The Non-N6-Methyladenosine Epitranscriptome Patterns and Characteristics of Tumor Microenvironment Infiltration and Mesenchymal Transition in Glioblastoma

Abstract: BackgroundAn increasing number of RNA modification types other than N6-methyladenosine (m6A) modification have been detected. Nonetheless, the probable functions of RNA modifications beyond m6A in the tumor microenvironment (TME), mesenchymal (MES) transition, immunotherapy, and drug sensitivity remain unclear.MethodsWe analyzed the characteristics of 32 non-m6A RNA modification regulators in 539 glioblastoma (GBM) patients and the TME cell infiltration and MES transition patterns. Using principal component an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 86 publications
(89 reference statements)
1
10
0
Order By: Relevance
“…In pathologic analysis, we found that HGGs had higher KDELR1 expression than LGGs. In addition, previous studies (35)(36)(37) have demonstrated that mesenchymal-subtype gliomas are associated with poor prognosis, which are confirmed by our finding that mesenchymal -subtype gliomas had a higher expression level of KDELR1 than proneural subtype gliomas. Subsequently, we further explored whether the expression of KDELR1 is related to recurrence.…”
Section: Discussionsupporting
confidence: 90%
“…In pathologic analysis, we found that HGGs had higher KDELR1 expression than LGGs. In addition, previous studies (35)(36)(37) have demonstrated that mesenchymal-subtype gliomas are associated with poor prognosis, which are confirmed by our finding that mesenchymal -subtype gliomas had a higher expression level of KDELR1 than proneural subtype gliomas. Subsequently, we further explored whether the expression of KDELR1 is related to recurrence.…”
Section: Discussionsupporting
confidence: 90%
“…Generally, M1-type macrophages play pro-inflammatory and anti-tumor functions, but tumor-associated macrophages (TAMs) in the TME are M2-type. Xu et al (2021a) elucidated the mechanism by which hypoxia and glioma affected autophagy and M2-like macrophage polarization through exosomes, thereby promoting the formation of an immunosuppressive microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…There are over 150 known RNA modifications, which include N6-methyladenosine (m6A), N7-methylguanosine (m7G), 5-methylcytidine (m5C), pseudouridine (Ψ), N6,2′-O-dimethyladenosine (m6Am), N1-methyladenosine (m1A), alternative polyadenylation (APA), 2′-O-methylated nucleotides (Nm), N4-acetylcytidine (ac4C), adenosine-to-inosine RNA editing (I), and cytidine-to-uridine RNA editing (U), all of which contribute to normal development and homeostasis and their dysregulation is known to cause various diseases including cancer ( Boccaletto et al, 2022 ; Zhao et al, 2017b ; Frye et al, 2018 ; Roundtree et al, 2017 ; Barbieri et al, 2017 ; Barbieri and Kouzarides, 2020 ). Previous studies have focused more on m6A, one of the most common modified forms in eukaryotic cells, which have been demonstrated to play a role in embryogenesis, neurogenesis, hematopoiesis, and tumorigenesis in some studies ( Zhao et al, 2017a ; Zhang et al, 2017 ; Barbieri et al, 2017 ; Xu et al, 2021a ). However, in recent years, modifications in non-m6A forms have also attracted increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal circumstances, it is now widely accepted that immune cells in the tumor microenvironment (TME) can distinguish and eradicate cancer cells, which is referred to as immunosurveillance ( 12 , 14 ). However, cancer cells can modulate the host immune system to evade immune surveillance by recruiting immunosuppressive cell populations and downregulating tumor immunogenicity ( 15 , 16 ). Stemness is used to evaluate the similarity of tumor cells to stem cells ( 17 ).…”
Section: Introductionmentioning
confidence: 99%